Review of Supporting Facilities for Intermodal Integration at Tanjung Kalian Ferry Port, Bangka Belitung Islands Province - Rahmita, Destria; Firzatullah, Raden Muhamad; Latuheru, Paulina Mutiara; Amanda, Monica; Zufar, Muhammad (IWTJ : International Water Transport Journal, 2023)
Tanjung Kalian Ferry Port has 14 ferry boats and 2 Damri buses at the port. Ferries docking at the port with Damri buses result in intermodal integration in supporting transportation services. However, there are several problems in this integration, such as the lack of waiting areas for service users, unavailable information on fares and schedules, and the need for special lanes for buses. This study aims to determine the condition of supporting facilities for intermodal integration and the fulfillment of these facilities. This study uses observation and documentation methods, it was found that currently the supporting facilities for integration are still inadequate. There are no waiting areas available, information on fares and schedules is not yet available, and the sidewalks at the port are inadequate for pedestrians. Therefore, it is recommended to plan the construction of a bus stop with a size of 23m x 7m, add information boards inside the bus stop and post 2, improve the sidewalks inside and in front of the port (each with a width of 1.52 meters and 1.54 meters), and add no parking signs at the pedestrian exit.